"About the opening of the Kostanay Pedagogical College" From the history of pedagogical education in Kazakhstan in the 1920s – early 1930s (Journal of history, 2023)
The article highlights the activities of the first pedagogical college in Kustanai (Kostanay) (known as the "pedagogical school" or “teacher’s training school”), opened a hundred years ago after the end of the civil war, like other similar educational institutions in the Kazakh ASSR in the middle of the 1920s. The purpose of the article is to investigate the training, cultural and educational activities, defense mass work in the technical school with the biographical data of its leaders and teachers. Information on the receipt of special pedagogical education by graduates of Kazakh schools, on the financial situation of students is provided. The weak financial support of the pedagogical college from the higher authorities is shown. In fact, the high turnover of the contingent of students periodically led to the disruption of preparation plans for each new academic year, it was the case with teacher courses organized at the pedagogical college for the Kazakh and Russian groups. As a result of the analysis of the work of departments of public education, the inconsistency of the Soviet policy in the training of national personnel is revealed; on the one hand, from the 1920s to the early 1930s a course of “indigenization” was carried out, and on the other hand, graduates of Kazakh schools were deprived of the right to receive pedagogical education. The repressive policy in the field of public education, the exclusion from teaching of persons who opposed the Soviet regime during the civil war, the expulsion of students from the technical school on a class basis are highlighted, and the role of exiled teachers in the educational activities of the school is shown. The article is illustrated with archival photographs taken in the 1920s – early 1930s.